Non-Critical Waveguide Alignment for Vertically-Coupled Microring using a Mode-Expanded Bus Architecture - TEE, Chyng Wen (Institutional Knowledge at Singapore Management University, 2006)
Vertically coupled microrings in an all-pass filter configuration are fabricated with a range of waveguide misalignments deliberately introduced into the lithography masks to demonstrate noncritical fabrication requirements. The microrings have a mode-expanded bus design which allows a greatly reduced variation in power coupling coefficient-only 6% for fabrication misalignments as high as 1 mum. This represents a five-fold improvement in fabrication tolerance when compared with conventional designs.